INFLUENCE PARENTAL INCOME ON GIRL CHILD EDUCATION IN PUBLIC SECONDARY SCHOOLS IN TURKANA NORTH SUB COUNTY, TURKANA COUNTY, KENYA - Aregae , Clare Ebenyo; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
Turkana County has more cases reported on girl child education being inevitable. The county continues to fall short when it comes to educating girls. In comparison to girls, boys predominate secondary education schooling. In addition, the county has few girl schools. Thus, the purpose of the study was to assess the influence parental income on girl child education in public secondary schools in Turkana North sub county, Turkana County, Kenya. It adopted a descriptive survey research design, with a target population of 348 persons, this comprised of 321 form four girls, 10 form four teachers, 5 form four principals, and 12 form four PTA parent members. The sample size of 186 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by the supervisors. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analyzed for the two scores and found to be 0.78, thus, the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics, and presented in tables, while, qualitative data was analyzed using the common themes, qualitative data extracted, organized, and then discussed under the main objective areas of the study. This was later presented by use of quotations. The study established that family factors like parental income, home tasks, family size and parental education influence girl child education in public secondary schools. The study recommended that head teachers, administration, policy makers and other stakeholders should consider family factors such as parental income as this will determine girl child education in public secondary schools. The information provided by this study will benefit policymakers, community members and academicians.